Platelet-rich plasma with versus without hyaluronic acid for hip osteoarthritis: a systematic review and meta-analysis - Santiago, Michael Silveira; Doria, Felipe Meireles; Morais Sirqueira Neto, José; Fontes, Fabio França; Porto, Erick Sobral; Aidar, Felipe J.; Silva, Marcus Vinicius Vieira de Matos Pereira; Cavalcante, Deivyd Vieira Silva; Akbarpoor, Fatemeh; Zamora, Fernanda Valeriano; Souza, Davi Teixeira de; Madruga, Reuthemann Esequias Teixeira Tenorio Albuquerque; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundThe use of intra-articular orthobiologics in hip osteoarthritis (HOA) has been presented as a therapeutic option and to postpone arthroplasty. There is little scientific evidence on the clinical application of platelet-rich plasma (PRP) associated with hyaluronic acid as dual therapy. Thus, the aim of our systematic review is to compare the clinical improvement with the use of PRP with versus without hyaluronic acid (HA) in hip osteoarthritis.MethodsWe systematically searched Cochrane, PubMed, and Embase databases for studies evaluating patients with HOA who received PRP with vs. without HA. Pain and functional score were collected and pooled at 3-, 6-, and 12-months follow-up. Mean differences (MD) and 95% intervals were calculated, and heterogeneity was assessed using I2 statistics. All statistical analysis was performed using R with the meta package.ResultsWe included 2 randomized controlled trials (RCTs) and 1 cohort study, comprising 190 patients, of whom 88 received the PRP plus HA. Relative to PRP alone, dual therapy led to significantly higher pain scores at 3 months (SMD 0.35; 95% CI 0.06 to 0.64; p < 0.01; I2 = 0%) and at 12 months (MD 11.92 points; 95% CI 3.87 to 19.97; p < 0.01; I2 = 0%), translating into worsening of pain including HA. There was no difference between groups at any follow-up regarding functional score or pain at 6 months.ConclusionJoint infiltration in HOA with PRP combined to HA showed higher perception of pain scores. Our findings suggest that the addition of HA in PRP treatment does not bring significant improvement and worsens patients’ quality of life. However, more randomized trials with larger populations may increase robustness.Systematic Review Registrationidentifier, CRD42024581335